FACTORS AFFECTING THE RELATIONSHIP OF DOMESTIC VIOLENCE PERPETRATORS - Nanci Yosepin Simbolon; Ediwarman Ediwarman; Madiasa Ablisar; Rosmalinda Rosmalinda (Green Publisher, 2023)
Domestic violence is generally carried out by the person closest to the victim and the husband is the dominant person being the perpetrator of violence against the wife. This can occur because family awareness has not been touched in improving self-quality through the application of understanding family functions. Victims of Domestic Violence also frequently exhibit mental health situations associated with a history of trauma to violence in their family. The depiction that men are considered more powerful and stronger makes them more aggressive, which can lead to domestic violence against women. The power relations of the perpetrators are also influenced by the wife's economic independence. The power of the perpetrator which is higher than the victim is influenced by the domination of the perpetrator in the economic system. Because the husband spends time in the sector that makes money while the wife takes care of the household and takes care of the children. The pattern of husband-wife relations greatly affects the roles between husband and wife and the distribution of power. Scanzoni and Scanzoni divide the husband-wife relationship into four types of marriage patterns, namely; property owner pattern, head complement pattern, senior-junior pattern, and equal partner pattern. These four patterns result from special and dynamic socio-economic conditions. Equal distribution of power in the family will have a low level of conflict of control, and violence